Tracking of Covid-19 in Libya - Aisha Nasef; Adel El Taguri (Studies on Stem Cells Research and Therapy - Peertechz Publications, 2020)
We read with interest the article entitled "Preliminary epidemiological analysis of suspected cases of corona infection in Libya" published in your journal by Dr. Daw MA. We have questions and comments on this paper in order to clarify and specify certain issues.